PROBLEMS OF INTRODUCTION OF CONTROL MODEL OF ELECTRONIC INFORMATION-EDUCATIONAL ENVIRONMENT IN FULL-TIME EDUCATION - N. Unizhayev (Вестник университета)
The research was allowed to formulate a model of management of electronic information and educational environment in full-time education and to identify the factors, affected to the introduction of advanced technologies in the educational processes of universities. The model takes into account the basic principles on which modern original courses may build. Interaction organization between the headquarters, forming the strategic development and the higher-education training, personnel on the issues, related to electronic information and educational environment, offered to shift responsibility to a dedicated structure. They will include specialists with professional competencies, related to the use of customer relationship management (CRM), specialized in management training courses and having experience in the use of new information technologies. The model has the flexibility and can be transformed to fit into every structure of university. The model involves the use of the help system.